Javanese local wisdom values for development from an Islamic perspective - Soya Sobaya; Martini Dwi Pusparini; Siti Achiria (Department of Islamic Economics, Islamic University of Indonesia, 2023)
IntroductionJavanese culture was considered rich of values that are in line with Islamic teachings. However, studies on how this culture can contribute to development in Islamic perspective are still limited.ObjectivesThis study analyzes the local wisdom values in Javanses culture that support economic development from an Islamic perspective. The studied values are contained in the traditions of merti dusun, nyadran, and wiwitan. MethodThis study using an ethnographic approach with focus is on three villages in Bantul, Yogyakarta. Interviews, observation, field notes were used to gather data. Three phases were used to complete the analysis: data reduction, reporting, and conclusion-making. ResultsThe findings demonstrate that each ritual in this tradition is infused with religious and social ideals, as well as cooperation, environmental stewardship, responsibility, patience, harmony, and deliberation. It also demonstrates wisdom and social control. ImplicationsThree traditions' emphasis on tolerance should be promoted to help people in their particular communities develop a greater sense of empathy for one another, fostering harmony and peace.Originality/NoveltyThis study highlights unique aspect of development that encompass Javanese culture and Islamic teachings.